PROPERTIES OF THE GLYCYRRHIZA GLABRA PLANT AND THE OBTAINMENT OF GLYCYRRHIZIC ACID SALTS AND THEIR CHEMICAL STRUCTURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article presents information on the biology, properties, folk medicinal uses of the plant Glycyrrhiza glabra, and the extraction of technical glycyrrhizic acid (TGK), triammonium glycyrrhizic acid (GKUAT), monoammonium glycyrrhizic acid (GKMAT), and monopotassium glycyrrhizic acid (GKMKT) salts from the liquid extract of its roots, as well as their chemical composition and structure.